Complete adult neurogenesis within a Wallerian degenerating nerve expressed as an ectopic ganglion. (10th May 2018) - Nakano, Tomonori; Kurimoto, Shigeru; Kato, Shuichi; Asano, Kenichi; Hirata, Takuma; Kiyama, Hiroshi; Hirata, Hitoshi
Abstract: Neurogenesis in the adult peripheral nervous system remains to be demonstrated. We transplanted embryonic neural stem cells into a Wallerian degenerating nerve graft and observed development of a nodular structure consisting of neurons, glia, and Schwann cells. Histological analysis revealed a structure loosely resembling the spinal cord, including a synaptic network that formed along the neuron. Furthermore, the new axons reinnervated the paralysed muscle, forming both de novo and revived neuromuscular junctions. Reinnervation of the paralysed muscle resulted in significantly greater mean wet muscle weight and muscle fibre cross‐sectional area on the cell transplantation side than on the surgical control side (body weight 0.071 ± 0.011% vs. 0.051 ± 0.007%, p  = .006; area 355.6 ± 345.2 vs. 114.0 ± 132.0 μm 2, p  < .001). Electrophysiological experiments demonstrated a functional connection between the neurons and muscle; hence, we identified this nodule as an ectopic ganglion. Surprisingly, in green rat experiments, most of these glial cells, but none of the neurons, expressed enhanced green fluorescent protein, suggesting that the cells constituting the ectopic ganglion were derived from both transplanted stem cells and endogenous stem cells. Such adult neurogenesis in a peripheral nerve related to neural stem cell transplantation has not been reported previously, and these results form the basis for a novel regenerative medicine approach in paralysed muscle.